Blockchain for committing peer-to-peer transactions using distributed ledger technologies. (4th June 2021) - Sarode, Rashmi P.; Poudel, Manoj; Shrestha, Shashank; Bhalla, Subhash
Blockchain consists of networks of successive blocks that are interconnected to each other by references to their former block. These form a chain. Blockchain technology creates a database like support by creation of digital ledgers, in order to support distributed transactions. The adoption of blockchain in real-world applications poses many challenges. This study aims to understand the method, its characteristics as well as the implementation concepts of transactional systems in terms of distributed transactions over web resources. The study also examines the current trends and issues in the use of blockchain in many large-scale public utility applications in e-commerce.